The effects of acid and alkaline solutions on cut marks and on the structure of bone: An experimental study on porcine ribs. Issue 6 (November 2015) - Amadasi, Alberto; Camici, Arianna; Sironi, Luca; Profumo, Antonella; Merli, Davide; Mazzarelli, Debora; Porta, Davide; Duday, Henri; Cattaneo, Cristina
Graphical abstract: Highlights: Little is yet known about the action of acid or basic solutions to human tissues. The effects of different pH (from 1 to 14) was investigated on cut marks and on the structure of bone. The features of cut marks on bone may be severely affected by extremely basic substances. The osteonic structure of bone undergoes several changes like crackings, detectable microscopy. Abstract: Among taphonomical modifications during decomposition processes, little is known about the action of high or low pH to human tissues and bones. Moreover, acid or basic solutions are seldom used to ease decomposition and wrecking of the body. In this study a total of 60 samples of porcine bones on which two cut marks were produced before the beginning of the experiment, were put in six different solutions with different pH (1, 3, 5, 9, 12, 14) and analyzed every five days over a period of 70 days. Surveys were carried out macroscopically, with stereomicroscopy and with light microscopy on thin sections. Only the specimens exposed to extremely acid (<1) or basic (>12) pH showed evident modifications of the bone's structure, as witnessed by the analyses with stereomicroscopy as well. Many samples showed a detachment of the periosteum; cut marks became soon unrecognizable with pH 14 but still detectable in all the other samples. The information gained from the present study can be of great help in detecting the exposure of human tissues to high or low environmental pH and in understanding the effects that these solutions can exert on human bones.